A deafness-associated mitochondrial DNA mutation caused pleiotropic effects on DNA replication and tRNA metabolism. Issue 16 (30th August 2022) - Meng, Feilong; Jia, Zidong; Zheng, Jing; Ji, Yanchun; Wang, Jing; Xiao, Yun; Fu, Yong; Wang, Meng; Ling, Feng; Guan, Min-Xin
Abstract: In this report, we investigated the molecular mechanism underlying a deafness-associated m.5783C > T mutation that affects the canonical C50-G63 base-pairing of TΨC stem of tRNA Cys and immediately adjacent to 5′ end of light-strand origin of mitochondrial DNA (mtDNA) replication (OriL). Two dimensional agarose gel electrophoresis revealed marked decreases in the replication intermediates including ascending arm of Y-fork arcs spanning OriL in the mutant cybrids bearing m.5783C > T mutation. mtDNA replication alterations were further evidenced by decreased levels of PolγA, Twinkle and SSBP1, newly synthesized mtDNA and mtDNA contents in the mutant cybrids. The m.5783C > T mutation altered tRNA Cys structure and function, including decreased melting temperature, conformational changes, instability and deficient aminoacylation of mutated tRNA Cys . The m.5783C > T mutation impaired the 5′ end processing efficiency of tRNA Cys precursors and reduced the levels of tRNA Cys and downstream tRNA Tyr . The aberrant tRNA metabolism impaired mitochondrial translation, which was especially pronounced effects in the polypeptides harboring higher numbers of cysteine and tyrosine codons. These alterations led to deficient oxidative phosphorylation including instability and reduced activities of the respiratory chain enzyme complexes I, III, IV and intact supercomplexes overall. Our findings highlight the impact of mitochondrial dysfunction on deafness arising from defects in mitochondrial DNA replication and tRNA metabolism.